Inovasi Layanan Elektronik Mobile Perekaman dan Aktivasi Indentitas Kependudukan Digital Penduduk Desa (Lemper Pedes) di Kecamatan Balongbendo, Sidoarjo - Ramadhani, Intan Putri; Fanida, Eva Hany; M, Meirinawati; Oktariyanda, Trenda Aktiva (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Public service is a form of government responsibility in fulfilling the needs of the community for goods, services and services. However, in its implementation, public services still experience many problems, so that effective and efficient public services have not been achieved and fulfilled. The Sidoarjo Regency Government is one of the regions that actively develops innovation, through a competition called Kisi (Sidoarjo Innovation Competition) and One of the Districts participating in this competition is Balongbendo District by creating an innovation Patas (Sub-district Services in Villages). The purpose of this study is to analyze and describe the Lemper Pedes Innovation in Balongbendo District, Sidoarjo with a qualitative approach and descriptive method where data collection is through documentation, interviews and observations. The results of the study indicate that the Lemper Pedes Innovation has been running well, although several indicators have not been optimal due to still facing obstacles related to internet network stability, the gap in community ability and access in using smartphones, lack of socialization for the community, minimal budget allocation for equipment maintenance and upkeep, and the lack of a systematic and documented evaluation system.